Fully Screen‐Printed Tunable Microwave Components Based on Optimized Barium Strontium Titanate Thick Films. (17th June 2014) - Kohler, Christian; Nikfalazar, Mohammad; Friederich, Andreas; Wiens, Alex; Sazegar, Mohsen; Jakoby, Rolf; Binder, Joachim R.
Abstract : The composite system Ba0.6 Sr0.4 TiO3 –ZnO–B2 O3 for thick film preparation has been modified via copper–fluorine codoping of BST to make it suitable for the fabrication of co‐fired metal‐insulator‐metal (MIM) components. Based on the resulting improvement of the thick films, MIM varactors and phase shifters were produced by subsequent screen‐printing of silver and BST pastes as well as co‐firing. Microstructural investigations showed the compatibility of silver and BST with neither chemical reaction nor cracking of the layers. The microwave characterization revealed good results regarding tunability and quality factor of the varactors and high figure of merit of 70°/dB at 1.72 GHz for the phase shifter.